2020
DOI: 10.2147/ott.s250412
|View full text |Cite
|
Sign up to set email alerts
|

<p>GRHL2 Upregulation Predicts a Poor Prognosis and Promotes the Resistance of Serous Ovarian Cancer to Cisplatin</p>

Abstract: Background: GRHL2 has been shown to function in ovarian carcinogenesis. However, the relationship between GRHL2 and cisplatin (DDP) resistance in serous ovarian cancer (SOC) is not clear. The purpose of this study was to elucidate the function and mechanism of GRHL2 in DDP resistance of SOC. Materials and Methods: Immunohistochemistry (IHC) was utilized to identify GRHL2 protein expression in DDP resistant and sensitive SOC tissues. GRHL2 mRNA and protein levels were identified using quantitative real-time PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…GRHL2 is involved in EMT through CLDN4 core promoter and E-cadherin gene regulation ( 45 ). Gynecological tumor studies have also demonstrated that increased GRHL2 expression is associated with poor prognosis in ovarian cancer ( 46 ). RARRES2 is a small, secreted protein associated with a variety of cancers, and higher serum RARRES2 levels have been shown to be associated with improved overall survival in adrenocortical tumors ( P = 0.0227) ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…GRHL2 is involved in EMT through CLDN4 core promoter and E-cadherin gene regulation ( 45 ). Gynecological tumor studies have also demonstrated that increased GRHL2 expression is associated with poor prognosis in ovarian cancer ( 46 ). RARRES2 is a small, secreted protein associated with a variety of cancers, and higher serum RARRES2 levels have been shown to be associated with improved overall survival in adrenocortical tumors ( P = 0.0227) ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitive and resistant patients were defined as follows: patients who developed progressive disease within 6 months after initial treatment were defined as cisplatin resistant; the other patients were defined as cisplatin sensitive. 14 Adjacent normal tissues served as the N group (n=70). Tumor tissues obtained from cisplatin-resistant patients were used as the R group (n=38).…”
Section: Clinical Tissuesmentioning
confidence: 99%
“…Previous reports revealed that ERK/MAPK actively participated in the development of chemoresistance to multiple drugs during chemotherapy for human cancers [24][25][26]. Besides, Raghav et al elucidated the ERK/MAPK pathway activated by HGF/MET axis could animate oncogenic signaling in CTX-resistant tumors to further aggravate chemoresistance [27], indicating that ERK/MAPK signaling contributed to CTX resistance in tumors.…”
Section: Lmtk3 Activates Erk/mapk Pathway In Ctx-resistant Crc Cellsmentioning
confidence: 99%